Teh Hitam Cammelia Sinensis dan Manfaatnya Untuk Kesehatan Pendekatan Berbasis Sains dan Nilai Islam - Putri, Ivvani Aulia; Sholikah, Siti Amanatus; Mubasyiroh, Mubasyiroh; Prasetyo, Oky Bagas; Aini, Nur; Yulianti, Eny (Es-Syajar:Journal of Islam, Science and Technology Integration, 2024)
Black tea from Camellia sinensis has been a highly popular beverage in Indonesia since the 17th century. Various types of Camellia sinensis tea include white tea, green tea, oolong tea, and black tea. Each type of tea has a distinct antioxidant profile, with black tea containing the highest caffeine content. All types of tea are rich in antioxidants like polyphenols, which play a crucial role in protecting the body from free radicals and reducing the risk of various diseases such as Alzheimer's, diabetes, stroke, hypertension, obesity, cancer, and have antibacterial properties while also serving as an anti-aging treatment for the skin.From an Islamic perspective, the Quran contains numerous verses that command humans to observe and study Allah's creations. This underscores the belief that nothing Allah has created is without purpose, implying that every creation has significant benefits. The consumption of black tea aligns with the principle of maintaining physical health as a form of spiritual responsibility, as also instructed in the Quran. The integration of scientific approaches with religious values elevates black tea beyond merely a beverage enjoyed for its taste, tradition, and health benefits, making it a part of a holistic healthy lifestyle. Utilizing tea production technology and advancing research to uncover the benefits of black tea is a way of expressing gratitude and is considered an act of worship, as its development adheres to the principle of benefiting others.